Transgression in and of the City. (November 2013) - Altay, Can; Mosley, Jonathan; Sara, Rachel
Abstract For Turkish artist and educator Can Altay 'today's cities are full of limits'. This unevenness can be regarded as the manifestation of current investment patterns and political and cultural conflicts. Does, however, transgression offer opportunities to subvert this? Is it possible for a city's inhabitants, artists and architects to open up boundaries and through the power of presence to intervene in the status quo?